Does efficiency matter for competition? A case of dual banking industry - Nafisah Mohammed,; Junaina Muhammad,; Abdul Ghafar Ismail,; Azmafazilah Jauhari, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study provides new empirical evidence on the link between bank performance measured in terms of efficiency, and the degree of competition in the Malaysian dual banking market which comprises Islamic and conventional banking systems over the period of 1997-2016. The focal point of this study is to investigate whether the type of efficiency matters for banks in remaining viable in the highly competitive market. The study on this subject is important because it compares the effect of market conditions and banks’ conduct on the level of competition for Islamic and conventional banking industries. In this study, we utilize the Panzar-Rosse (PR) H-statistics to represent the competition index. In addition, the Data Envelopment Analysis (DEA) is used to calculate the income and cost efficiencies for the banks in both banking systems. This study employs a panel data model with pooled Ordinary Least Square (OLS) to estimate the relationships of competition index with efficiency scores, concentration indexes, and other bank-specific variables. The estimation results show the existence of a positive relationship between types of efficiency and competition in the dual banking market. This evidence suggests that the existence of an ideal level of concentration and competition is important for banks in adjusting their behavior to suit market conditions and to operate efficiently. Policymakers and regulators may use the knowledge of market structure and performance from this study to formulate policies and strategies that will optimize the number of banks operating in the industry. Policymakers, through Bank Negara Malaysia (BNM), should thus consider the relationship between market structure and bank performance to formulate policies and strategies that will optimize the number of banks operating in the industry.